The Relationship Between Parent's Work Stress with Verbal Violence on Early Childhood In Batik Production Area, Lasem District, Rembang Regency - Listari, Listari; Astuti, Henny Puji (Jurusan PGPAUD FIP UNNES, 2021)
Lasem is one of the sub-districts in Rembang Regency which consists of several villages whose residents work as batik artisans. Many housewives in the sub-district choose to work even though they have early children so that parents have difficulty supervising children while working. If parents are faced with the demands of a lot of work or are unable to manage the time between work and household care, it will cause work stress that can result in verbal violence when caring for children. The purpose of this study is to examine the relationship between work stress of parents with verbal violence against young children in the Handwritten Batik District of Lasem District, Rembang Regency. This study uses a correlational quantitative research method using two scales, the Work Stress Scale and the Verbal Hardness Scale. The population in this study is children aged 4-6 years whose parents worked as batik makers in the Handwritten Batik Area of Lasem District, Rembang Regency. The number of samples in this study is 32 children aged 4-6 years. The sampling technique in this study is the purposive sampling technique. The data analysis technique is using a product-moment correlation test with SPSS Program Version 23. The results showed that parents' work stress had a significant positive relationship toward verbal abuse against early childhood. The correlation coefficient of the two variables is 0.427 and the significance value is 0.015 <0.05. This implies that the higher the work stresses of parents, the higher the verbal abuse against early childhood. Conversely the lower the work stresses of parents, the lower the verbal abuse against early childhood.